2020
DOI: 10.3389/fpsyg.2020.02118
|View full text |Cite
|
Sign up to set email alerts
|

Immersion, Absorption, and Spiritual Experience: Some Preliminary Findings

Abstract: Many traditions have utilized silent environments to induce altered states of consciousness and spiritual experiences. Neurocognitive explorations of spiritual experience can aid in understanding the underlying mechanism, but these are surprisingly rare. We present the verbal report and the electroencephalographic (EEG) alpha profile of a female participant scoring a maximal 34 on the Absorption Scale, recorded before and while she was immersed in a whole-body perceptual deprivation (WBPD) tank. We analyze her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Indeed, as noted in the Introduction, this is perhaps not wholly surprising, as trait absorption has been found to predict mystical and quasi-mystical experiences produced endogenously in certain sensory-depriving, homeostasis-unbalancing, and trance-inducing contexts (Rock, 2009 ; Luhrmann et al, 2010 ; Bronkhorst, 2016 ; Luke et al, 2018 ; Glicksohn and Ben-Soussan, 2020 ), as well as some of the common characteristics of spiritual states associated with SSA/SKAs, such as stronger empathy (Wickramasekera and Szlyk, 2003 ; Wickramasekera, 2007 ), stronger flow states (Marty-Dugas and Smilek, 2019 ), more pronounced creativity (Wild et al, 1995 ; Manmiller et al, 2005 ), a stronger attachment to nature and other forms of life (Kaplan, 1995 ; Brown and Katcher, 1997 ), feelings of self-transcendence (Cardeña and Terhune, 2014 ), more pronounced experiences of synaesthesia (Rader and Tellegen, 1987 ; Glicksohn et al, 1999 ; Chun and Hupé, 2016 ), alterations in time-space perception and meaning (Pekala et al, 1985 ; Kumar and Pekala, 1988 ), and paranormal beliefs or experiences (Glicksohn, 1990 , 2004 ; Spanos et al, 1993 ; Glicksohn and Barrett, 2003 ; Granqvist et al, 2005 ; French et al, 2008 ; Parra, 2008 ; Zingrone et al, 2009 ; Luhrmann et al, 2010 , 2021 ; Gray and Gallo, 2016 ; Parra and Gimenez Amarilla, 2016 ), in drug and non-drug contexts relative to the general population. The differences in measured predictions of SSA/SKA intensity between TLL and absorption are likely due to the fact that each dependent variable used in our study measured slightly different aspects of overall SSA/SKA experiences (i.e., kundalini awakening, nondual experience, mystical experience, ASC).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Indeed, as noted in the Introduction, this is perhaps not wholly surprising, as trait absorption has been found to predict mystical and quasi-mystical experiences produced endogenously in certain sensory-depriving, homeostasis-unbalancing, and trance-inducing contexts (Rock, 2009 ; Luhrmann et al, 2010 ; Bronkhorst, 2016 ; Luke et al, 2018 ; Glicksohn and Ben-Soussan, 2020 ), as well as some of the common characteristics of spiritual states associated with SSA/SKAs, such as stronger empathy (Wickramasekera and Szlyk, 2003 ; Wickramasekera, 2007 ), stronger flow states (Marty-Dugas and Smilek, 2019 ), more pronounced creativity (Wild et al, 1995 ; Manmiller et al, 2005 ), a stronger attachment to nature and other forms of life (Kaplan, 1995 ; Brown and Katcher, 1997 ), feelings of self-transcendence (Cardeña and Terhune, 2014 ), more pronounced experiences of synaesthesia (Rader and Tellegen, 1987 ; Glicksohn et al, 1999 ; Chun and Hupé, 2016 ), alterations in time-space perception and meaning (Pekala et al, 1985 ; Kumar and Pekala, 1988 ), and paranormal beliefs or experiences (Glicksohn, 1990 , 2004 ; Spanos et al, 1993 ; Glicksohn and Barrett, 2003 ; Granqvist et al, 2005 ; French et al, 2008 ; Parra, 2008 ; Zingrone et al, 2009 ; Luhrmann et al, 2010 , 2021 ; Gray and Gallo, 2016 ; Parra and Gimenez Amarilla, 2016 ), in drug and non-drug contexts relative to the general population. The differences in measured predictions of SSA/SKA intensity between TLL and absorption are likely due to the fact that each dependent variable used in our study measured slightly different aspects of overall SSA/SKA experiences (i.e., kundalini awakening, nondual experience, mystical experience, ASC).…”
Section: Discussionmentioning
confidence: 90%
“…It has been found to be a good predictor of altered states produced by psychedelic substances (Haijen et al, 2018 ) such as psilocybin (Studerus et al, 2012 ; Studerus, 2013 ), LSD (Carhart-Harris et al, 2015 ; Terhune et al, 2016 ), MDMA (Hastings, 2006 ), ayahuasca (Bresnick and Levin, 2006 ), and ayahuasca's active ingredient, DMT (Timmermann et al, 2018 ). It is also a good predictor of mystical and quasi-mystical experiences produced endogenously in contexts such as the anechoic dark room (Luke et al, 2018 ), the whole-body perceptual deprivation tank (WBPD; Glicksohn and Ben-Soussan, 2020 ), and during guided “shamanic journey” visualisation (Rock, 2009 ). Traditionally, the trait has been associated with “fantasy proneness,” hypnotisability, imagery ability, openness to experiences (McCrae and Costa, 1983 ; Pekala et al, 1985 ; Roche and McConkey, 1990 ; Glisky et al, 1991 ), alterations in body image, time-space perception, and meaning (Pekala et al, 1985 ; Kumar and Pekala, 1988 ), higher emotional sensitivity and emotional brain processing (McCrae and Costa, 1983 ; Benning et al, 2015 ), stronger empathy (Wickramasekera and Szlyk, 2003 ; Wickramasekera, 2007 ), stronger flow states (Marty-Dugas and Smilek, 2019 ), intellectual curiosity (McCrae and Costa, 1983 ), more pronounced creativity and engagement in the arts (Wild et al, 1995 ; Manmiller et al, 2005 ), positive emotional responses to music (Rhodes et al, 1988 ), more pronounced experiences of synaesthesia (Rader and Tellegen, 1987 ; Glicksohn et al, 1999 ; Chun and Hupé, 2016 ), and an attachment to nature and other forms of life (Kaplan, 1995 ; Brown and Katcher, 1997 ), relative to the general population.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the alpha oscillation power increase on the right frontal area is correlated with spiritual experience during a sensory deprivation environment ( Glicksohn and Ben-Soussan, 2020 ). We did not find the alpha but theta power increase in frontal regions; no participant of our study reported any spiritual or mystic experience during the RB sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Dominating experience of being haunted by depression which perceptibly banishes one's selfidentity is likely to cause a loss of self-awareness, alongside pathological sequelae. Supporting fragmented selves, mindful ways in holistic healthcare are about to gain importance, spiritual immersion [46] included. The BARIT-model encompasses musical immersion, either through listening or music-making.…”
Section: Immersionmentioning
confidence: 99%